PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA: PENGARUH KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP PRODUKTIVITAS KERJA - Elba, Riskina Agustin; Efendi, Nur; Saptiani, Fenny (Jurnal Kompetitif Bisnis, 2023)
This study aimed to find out the effect of leadership on work productivity of Bank Bukopin KCULampung employees , to find out the effect of work environment on work productivity of Bank BukopinKCU Lampung enployees, and also to know the effect of leadership and work environment on workproductivity of Bank Bukopin KCU Lampung employees. Also, this study applied quantitative research.Furthermore, this study was conducted from January to April 2023. The population and sample of studyare 47 Bank Bukopin KCU Lampung employees. Moreover, primary and secondary data were used inthis study. The data were collected by distributing the questionnaire to the employees. Then, it wasanalyzed by using multiple linear regression analysis. Based on the result of research, it can beconcluded that leadership and work environment have positive and significant impacts on employees’work productivity by 54,0% and it was impacted by other factors not examined in this study such asmotivation, discipline, competence, and others.